A national economic and clinical model for ischemic stroke care development in Saudi Arabia: A call for change. Issue 8 (October 2019) - Al-Senani, Fahmi; Al-Johani, Mohammed; Salawati, Mohammad; ElSheikh, Souda; AlQahtani, Maha; Muthana, Jamal; AlZahrani, Saeed; Shore, Judith; Taylor, Matthew; Ravest, Valeska S; Eggington, Simon; Cuche, Matthieu; et al.
Background: Stroke is a significant burden in Saudi Arabia and the Saudi Ministry of Health's stroke committee has identified an urgent need to improve care. Aim: The purpose of this study was to undertake a health-economic analysis to quantify the impact of developing stroke care in the country. Methods: An economic model was developed to assess the costs and clinical outcomes associated with an ischemic stroke care development program compared with current stroke care. Based on Saudi epidemiological data, cohorts of ischemic stroke patients enter the model each year for the first 10 years based on increasing incidence. Four treatment options were modeled including reperfusion and non-reperfusion treatments. The development scenario estimates the impact of gradually increasing uptake of more effective treatments over 10 years. Changes in the stroke care organization are considered along with resources required to increase capacity, allowing more patients to be admitted to stroke hospitals and access effective treatments. Results: The stroke care development program is associated with an increase in functionally independent patients and a decrease in disabling strokes compared with current stroke care. Additionally, the development program is associated with estimated cost savings of 602 million over 15 years (255 million direct costs, 348 million indirect costs). Conclusions: The model predicts that the stroke care development program is associated with improved patient outcomes and lower overall costs compared with the current stroke care program.